Adhesive composition, pressure sensitive adhesive sheet and conjugate

By increasing the dielectric constant and capacitance density of the pressure-sensitive adhesive layer, the problem of insufficient weakening of the adhesive strength of the electroliberated adhesive in low-humidity environments is solved, and good electroliberation in winter and other environments is achieved.

JP2025061948APending Publication Date: 2025-04-11NITTO DENKO CORP

Patent Information

Application Number
JP2025013192
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-03-28
Filing Date
2025-01-29
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In low-humidity environments, the weakening rate of the adhesion strength of the electroliberating adhesive is insufficient, which makes it difficult to effectively peel off in low-humidity environments such as winter.

Method used

By increasing the dielectric constant relative to components other than ionic liquid, the dielectric constant of the pressure-sensitive adhesive layer is increased, and the capacitance density between the adhesive layer and the substrate is increased, and ionic conductivity is enhanced to enhance electroliberation.

Benefits of technology

In low humidity environments, the adhesion strength of the adhesive is significantly reduced after the voltage is applied, ensuring good electroliberation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061948000001_ABST
    Figure 2025061948000001_ABST
Patent Text Reader

Abstract

To provide an adhesive composition capable of lowering an adhesive strength sufficiently by applying a voltage even in a low humidity environment.SOLUTION: An adhesive composition at least includes a polymer and ionic liquid. An adhesive layer is formed by a composition composed of components other than the ionic liquid from among included components. The adhesive layer has a dielectric constant of 5 or more at a frequency 100 Hz after the adhesive layer has been left standing under an environment at 22°C and 20%RH for three days.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet including a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition, and a bonded body of the pressure-sensitive adhesive sheet and an adherend. [Background technology]

[0002] In electronic component manufacturing processes, etc., there is an increasing demand for rework to improve yields and recycling by disassembling and recovering components after use. In order to meet such demands, double-sided pressure-sensitive adhesive sheets that have a certain degree of adhesive strength as well as a certain degree of releasability are sometimes used to bond components in electronic component manufacturing processes, etc.

[0003] Known double-sided adhesive sheets that achieve the above-mentioned adhesive strength and releasability include adhesive sheets that use an ionic liquid consisting of cations and anions as a component that forms the adhesive composition, and that can be peeled off by applying a voltage to the adhesive layer (electrically peelable adhesive sheets) (Patent Documents 1 to 3). In the electrically peelable adhesive sheets of Patent Documents 1 to 3, it is believed that application of a voltage causes the cations of the ionic liquid to migrate to the cathode side, causing reduction, and the anions of the ionic liquid to migrate to the anode side, causing oxidation, weakening the adhesive strength at the adhesive interface and making the sheet more susceptible to peeling. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-037354 A [Patent Document 2] Patent No. 6097112 [Patent Document 3] Patent No. 4139851 Summary of the Invention [Problem to be solved by the invention]

[0005] It is preferable that the electrically peelable adhesive sheet firmly bonds members when no voltage is applied, and can be peeled off with little force when voltage is applied. Therefore, it is preferable that the adhesive strength of the electrically peelable adhesive sheet is reduced by a large rate due to the application of voltage. However, in a low humidity environment such as winter, the adhesive strength is reduced by the application of voltage, which is a problem.

[0006] The present invention has been completed in view of the above, and aims to provide an adhesive composition whose adhesive strength is sufficiently reduced by application of a voltage even in a low humidity environment, and an adhesive sheet having an adhesive layer formed from the adhesive composition. [Means for solving the problem]

[0007] According to the inventors' investigations, the reason why the rate of decrease in adhesive strength due to voltage application is smaller in a low humidity environment is because the moisture content of the adhesive layer decreases in a low humidity environment, making it difficult for the cations and anions of the ionic liquid to move. As a result of further investigations, the present inventors have obtained the following findings. First, it was found that the dielectric constant of the components other than the ionic liquid in the pressure-sensitive adhesive layer correlates with the rate of decrease in adhesive strength due to the application of voltage, and that the rate of decrease in adhesive strength due to the application of voltage can be increased by increasing the dielectric constant. It was also found that even when the pressure-sensitive adhesive layer is placed in a low-humidity environment and the moisture content decreases, if the dielectric constant is large, the electrical peelability is good, i.e., the rate of decrease in adhesive strength due to the application of voltage is large. Secondly, it was found that the ionic conductivity of the adhesive layer and the capacitance per unit area of ​​the interface between the adhesive layer and the adherend are correlated with the rate of decrease in adhesive strength due to the application of voltage, and that the rate of decrease in adhesive strength due to the application of voltage can be increased by increasing the ionic conductivity and the capacitance per unit area of ​​the interface between the adhesive layer and the adherend. It was also found that even when the adhesive layer is placed in a low humidity environment and the moisture content decreases, if the ionic conductivity and the capacitance per unit area of ​​the interface between the adhesive layer and the adherend are large, the electrical peelability is good, i.e., the rate of decrease in adhesive strength due to the application of voltage is large.

[0008] One pressure-sensitive adhesive composition of the present invention, which has been completed based on the above first finding, is a pressure-sensitive adhesive composition comprising a polymer and an ionic liquid, wherein an adhesive layer is formed from a composition consisting of components contained in the pressure-sensitive adhesive composition other than the ionic liquid, and after leaving the pressure-sensitive adhesive layer for 3 days in an environment of 22°C and 20% RH, the pressure-sensitive adhesive layer has a relative dielectric constant of 5 or more at a frequency of 100 Hz.

[0009] Another pressure-sensitive adhesive composition of the present invention, which has been completed based on the second finding, is a pressure-sensitive adhesive composition comprising a polymer and an ionic liquid, and when a pressure-sensitive adhesive layer is formed from the pressure-sensitive adhesive composition and attached to an aluminum plate made of A5052P H32 according to JIS H4000:2014, and left for 7 days in an environment of 22°C and 15% RH, the capacitance per unit area of ​​the interface between the pressure-sensitive adhesive layer and the aluminum plate is 0.9 μF / cm 2 The pressure-sensitive adhesive layer has an ionic conductivity of 10 μS / m or more.

[0010] In one embodiment of the pressure-sensitive adhesive composition of the present invention, a pressure-sensitive adhesive layer is formed from the pressure-sensitive adhesive composition, After being attached to an aluminum plate made of A5052P H32 according to S H4000:2014 and left for 7 days in an environment of 22°C and 15% RH, the capacitance per unit area of ​​the interface between the adhesive layer and the aluminum plate was 1.2μF / cm 2 Furthermore, the pressure-sensitive adhesive layer may have an ionic conductivity of 20 μS / m or more.

[0011] In one embodiment of the pressure-sensitive adhesive composition of the present invention, the pressure-sensitive adhesive composition may further contain an ionic solid.

[0012] In one embodiment of the pressure-sensitive adhesive composition of the present invention, the polymer may include an ionic polymer.

[0013] In one embodiment of the pressure-sensitive adhesive composition of the present invention, the polymer may include at least one selected from the group consisting of polyester-based polymers, urethane-based polymers, and acrylic polymers having a carboxyl group, an alkoxy group, a hydroxyl group, and / or an amide bond.

[0014] Another pressure-sensitive adhesive composition of the present invention contains a polymer and an ionic liquid, and contains 0.5 to 30 parts by mass of the ionic liquid and 0.5 to 10 parts by mass of the ionic solid per 100 parts by mass of the polymer.

[0015] Another pressure-sensitive adhesive composition of the present invention contains a polymer and an ionic liquid, and contains 0.5 to 30 parts by mass of the ionic liquid per 100 parts by mass of the polymer, and the polymer contains 0.05 to 2 parts by mass of an ionic polymer.

[0016] Another pressure-sensitive adhesive composition of the present invention is a pressure-sensitive adhesive composition comprising 100 parts by mass of an acrylic polymer and 0.5 to 30 parts by mass of an ionic liquid, in which the ratio of the polar group-containing monomer to all monomer components constituting the acrylic polymer is 0.1 to 35% by mass.

[0017] In one embodiment of the present invention, the pressure-sensitive adhesive composition is for electrical peeling.

[0018] The pressure-sensitive adhesive sheet of the present invention comprises a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention.

[0019] The bonded structure of the present invention comprises an adherend having a metal adherend surface and the pressure-sensitive adhesive sheet of the present invention, with the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet of the present invention bonded to the metal adherend surface. Effect of the Invention

[0020] The adhesive strength of the pressure-sensitive adhesive composition of the present invention decreases sufficiently upon application of a voltage even in a low humidity environment. [Brief description of the drawings]

[0021] [Figure 1]1 is a cross-sectional view showing an example of a pressure-sensitive adhesive sheet of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a laminate structure of the pressure-sensitive adhesive sheet of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view showing another example of the laminate structure of the pressure-sensitive adhesive sheet of the present invention. [Figure 4] FIG. 2 is a cross-sectional view showing an outline of the method for the 180° peel test in the examples. [Diagram 5] FIG. 13 is a side view of a composite sample for capacitance and ionic conductivity measurements. [Figure 6] FIG. 13 is a top view of a composite sample for capacitance and ionic conductivity measurements. [Figure 7] FIG. 1 is an equivalent circuit diagram of a composite sample for capacitance and ionic conductivity measurements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the preferred embodiments. However, the present invention is not limited to the preferred embodiments described below.

[0023] [Adhesive composition] The pressure-sensitive adhesive compositions of the first and second embodiments of the present invention both contain a polymer and an ionic liquid. An adhesive layer is formed from a composition consisting of components other than the ionic liquid among the components contained in the adhesive composition of the first embodiment, and after the adhesive layer is left to stand for 3 days in an environment of 22°C and 20% RH, the adhesive layer has a relative dielectric constant of 5 or more at a frequency of 100 Hz. In addition, a pressure-sensitive adhesive layer was formed from the pressure-sensitive adhesive composition of the second embodiment, and attached to an aluminum plate made of A5052P H32 according to JIS H4000:2014. After leaving the plate for 7 days in an environment of 22°C and 15% RH, the capacitance per unit area of ​​the interface between the pressure-sensitive adhesive layer and the aluminum plate was 0.9 μF / cm 2 The pressure-sensitive adhesive layer has an ionic conductivity of 10 μS / m or more. These pressure-sensitive adhesive compositions have the property that their adhesive strength decreases when a voltage is applied, and are therefore suitable as electrically peelable pressure-sensitive adhesive compositions. The above first and second embodiments are not exclusive, and some pressure-sensitive adhesive compositions may fall into both the first and second embodiments, while other pressure-sensitive adhesive compositions may fall into only one of the two. If the pressure-sensitive adhesive composition falls into either the first or second embodiment, the effect of the present invention can be achieved. These pressure-sensitive adhesive compositions will now be described.

[0024] In this specification, the first and second embodiments of the present invention may be collectively referred to as "the present embodiment." In this specification, the adhesive strength when no voltage is applied is sometimes referred to as "initial adhesive strength." Furthermore, a composition that contains components other than the ionic liquid among the components contained in the pressure-sensitive adhesive composition may be referred to as an "ionic liquid-free pressure-sensitive adhesive composition". Furthermore, a pressure-sensitive adhesive layer formed from an ionic liquid-free pressure-sensitive adhesive composition may be referred to as an "ionic liquid-free pressure-sensitive adhesive layer". In addition, the property of adhesive strength decreasing due to the application of voltage is called "electrical releasability," and a material may have "excellent electrical releasability" if its adhesive strength decreases significantly due to the application of voltage.

[0025] <Components of Pressure-Sensitive Adhesive Composition> (polymer) The pressure-sensitive adhesive composition of the present embodiment contains a polymer. In the present embodiment, the polymer is not particularly limited as long as it is a general organic polymer compound, and is, for example, a polymer or partial polymer of a monomer. The monomer may be one type of monomer or a mixture of two or more types of monomers. The partial polymer means a polymer in which at least a part of the monomer or monomer mixture is partially polymerized.

[0026] The polymer in the present embodiment is not particularly limited as long as it is normally used as an adhesive and has adhesiveness, and examples thereof include acrylic polymers, rubber polymers, vinyl alkyl ether polymers, silicone polymers, polyester polymers, polyamide polymers, urethane polymers, fluorine polymers, and epoxy polymers, etc. The polymers may be used alone or in combination of two or more kinds. In order to increase the dielectric constant of the components other than the ionic liquid in the obtained pressure-sensitive adhesive layer, to increase the ionic conductivity of the obtained pressure-sensitive adhesive layer and the capacitance per unit area of ​​the adhesive interface, and to improve the electrical peelability, it is preferable that the dielectric constant of the polymer is large. From this viewpoint, it is particularly preferable that the polymer in this embodiment contains at least one selected from the group consisting of polyester-based polymers, urethane-based polymers, and acrylic polymers having a carboxyl group, an alkoxy group, a hydroxyl group, and / or an amide bond. Since polyester-based polymers and urethane-based polymers have hydroxyl groups that are easily polarized at their terminals, and since acrylic polymers having a carboxyl group, an alkoxy group, a hydroxyl group, and / or an amide bond are easily polarized, a polymer with a relatively large dielectric constant can be obtained by using these polymers. The content of the polyester-based polymer and the acrylic polymer having a carboxyl group, an alkoxy group, a hydroxyl group, and / or an amide bond in the polymer of this embodiment is preferably 60% by mass or more in total, more preferably 80% by mass or more. In particular, in order to improve costs, productivity, and initial adhesive strength, the polymer in this embodiment is preferably an acrylic polymer. That is, the pressure-sensitive adhesive composition of the present embodiment is preferably an acrylic pressure-sensitive adhesive composition containing an acrylic polymer as the polymer.

[0027] The acrylic polymer preferably contains a monomer unit derived from a (meth)acrylic acid alkyl ester (the following formula (1)) having an alkyl group having 1 to 14 carbon atoms. Such a monomer unit is suitable for obtaining a large initial adhesive strength. Furthermore, in order to increase the relative dielectric constant of the components of the pressure-sensitive adhesive layer other than the ionic liquid, and to increase the ionic conductivity of the obtained pressure-sensitive adhesive layer and the capacitance per unit area of ​​the adhesive interface, thereby improving the electrical peelability, the alkyl group R b The number of carbon atoms is preferably small, particularly preferably 8 or less, and more preferably 4 or less. CH 2 =C(R a )COOR b (1) [R in formula (1)] a is a hydrogen atom or a methyl group, R b is an alkyl group having 1 to 14 carbon atoms.

[0028] Examples of (meth)acrylic acid alkyl esters having an alkyl group having 1 to 14 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, 1,3-dimethylbutyl acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylbutyl acrylate, and the like. Examples of the acrylate include n-butyl acrylate, n-ethylhexyl acrylate, n-octyl acrylate, n-isooctyl acrylate, n-ethylhexyl acrylate, n-nonyl acrylate, n-isononyl acrylate, n-decyl acrylate, n-isodecyl acrylate, n-dodecyl acrylate, n-tridecyl acrylate, and n-tetradecyl acrylate. Among them, n-butyl acrylate, 2-ethylhexyl acrylate, and n-isononyl acrylate are preferred. The (meth)acrylic acid alkyl ester having an alkyl group having 1 to 14 carbon atoms can be used alone or in combination of two or more kinds.

[0029] The ratio of the (meth)acrylic acid alkyl ester having an alkyl group having 1 to 14 carbon atoms to the total monomer components (100% by mass) constituting the acrylic polymer is not particularly limited, but is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more. When the ratio of the acrylic polymer is 70% by mass or more, it becomes easier to obtain a large initial adhesive strength.

[0030] The acrylic polymer preferably contains a monomer unit derived from a polar group-containing monomer copolymerizable therewith, in addition to a monomer unit derived from a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 14 carbon atoms, for the purpose of modifying cohesive strength, heat resistance, crosslinkability, etc. The monomer unit can provide crosslinking points and is suitable for obtaining a large initial adhesive strength. Furthermore, it is preferable to contain a monomer unit derived from a polar group-containing monomer from the viewpoint of increasing the relative dielectric constant of the components other than the ionic liquid in the pressure-sensitive adhesive layer, increasing the ionic conductivity of the resulting pressure-sensitive adhesive layer and the capacitance per unit area of ​​the adhesive interface, and improving the electrical peelability.

[0031] Examples of polar group-containing monomers include carboxyl group-containing monomers, alkoxy group-containing monomers, hydroxyl group-containing monomers, cyano group-containing monomers, vinyl group-containing monomers, aromatic vinyl monomers, amide group-containing monomers, imide group-containing monomers, amino group-containing monomers, epoxy group-containing monomers, vinyl ether monomers, N-acryloylmorpholine, sulfo group-containing monomers, phosphoric acid group-containing monomers, and acid anhydride group-containing monomers. Among them, from the viewpoint of excellent cohesiveness, carboxyl group-containing monomers, alkoxy group-containing monomers, hydroxyl group-containing monomers, and amide group-containing monomers are preferred, and carboxyl group-containing monomers are particularly preferred. Carboxyl group-containing monomers are particularly suitable for obtaining large initial adhesive strength. Polar group-containing monomers can be used alone or in combination of two or more.

[0032] Examples of the carboxyl group-containing monomer include acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid. Acrylic acid is particularly preferred. The carboxyl group-containing monomer may be used alone or in combination of two or more.

[0033] Examples of the alkoxy group-containing monomer include a methoxy group-containing monomer and an ethoxy group-containing monomer. Examples of the methoxy group-containing monomer include 2-methoxyethyl acrylate.

[0034] Examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, (4-hydroxymethylcyclohexyl)methyl (meth)acrylate, N-methylol (meth)acrylamide, vinyl alcohol, allyl alcohol, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether. In particular, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred. The hydroxyl group-containing monomers can be used alone or in combination of two or more.

[0035] Examples of the amide group-containing monomer include acrylamide, methacrylamide, N-vinylpyrrolidone, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N'-methylenebisacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, and diacetoneacrylamide. The amide group-containing monomer may be used alone or in combination of two or more kinds.

[0036] Examples of cyano group-containing monomers include acrylonitrile and methacrylonitrile.

[0037] Examples of the vinyl group-containing monomer include vinyl esters such as vinyl acetate, vinyl propionate, and vinyl laurate, with vinyl acetate being particularly preferred.

[0038] Examples of aromatic vinyl monomers include styrene, chlorostyrene, chloromethylstyrene, α-methylstyrene, and other substituted styrenes.

[0039] Examples of imide group-containing monomers include cyclohexylmaleimide, isopropylmaleimide, N-cyclohexylmaleimide, and itaconimide.

[0040] Examples of amino group-containing monomers include aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate.

[0041] Examples of epoxy group-containing monomers include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether.

[0042] Examples of vinyl ether monomers include methyl vinyl ether, ethyl vinyl ether, and isobutyl vinyl ether.

[0043] The ratio of the polar group-containing monomer to the total monomer components (100% by mass) constituting the acrylic polymer is preferably 0.1% by mass or more and 35% by mass or less. The upper limit of the ratio of the polar group-containing monomer is more preferably 25% by mass, more preferably 20% by mass, and the lower limit is more preferably 0.5% by mass, more preferably 1% by mass, and particularly preferably 2% by mass. When the ratio of the polar group-containing monomer is 0.1% by mass or more, cohesive force is easily obtained, so that adhesive residue is less likely to occur on the adherend surface after the pressure-sensitive adhesive layer is peeled off, and the electrical peelability is improved. In addition, when the ratio of the polar group-containing monomer is 30% by mass or less, it is easy to prevent the pressure-sensitive adhesive layer from excessively adhering to the adherend and causing heavy peeling. In particular, when the ratio is 2% by mass or more and 20% by mass or less, it is easy to achieve both releasability to the adherend and adhesion between the pressure-sensitive adhesive layer and other layers.

[0044] Furthermore, the monomer components constituting the acrylic polymer may contain a polyfunctional monomer in order to introduce a crosslinked structure into the acrylic polymer and make it easier to obtain the required cohesive strength.

[0045] Examples of polyfunctional monomers include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, divinylbenzene, and N,N'-methylenebisacrylamide. The polyfunctional monomers can be used alone or in combination of two or more.

[0046] The content of the polyfunctional monomer relative to the total monomer components (100% by mass) constituting the acrylic polymer is preferably 0.1% by mass or more and 15% by mass or less. The upper limit of the content of the polyfunctional monomer is more preferably 10% by mass, and the lower limit is more preferably 3% by mass. When the content of the polyfunctional monomer is 0.1% by mass or more, the flexibility and adhesiveness of the pressure-sensitive adhesive layer are easily improved, which is preferable. When the content of the polyfunctional monomer is 15% by mass or less, the cohesive force is not too high, and appropriate adhesiveness is easily obtained.

[0047] A polyester-based polymer is typically a polymer having a condensation structure of a polycarboxylic acid such as a dicarboxylic acid or its derivative (hereinafter also referred to as a "polycarboxylic acid monomer") and a polyhydric alcohol such as a diol or its derivative (hereinafter referred to as a "polyhydric alcohol monomer").

[0048] The polyvalent carboxylic acid monomer is not particularly limited, but examples thereof that can be used include adipic acid, azelaic acid, dimer acid, sebacic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, dodecenylsuccinic anhydride, fumaric acid, succinic acid, dodecanedioic acid, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, maleic acid, maleic anhydride, itaconic acid, citraconic acid, and derivatives thereof. The polyvalent carboxylic acid monomers can be used alone or in combination of two or more kinds.

[0049] The polyhydric alcohol monomer is not particularly limited, but examples thereof include ethylene glycol, 1,2-propylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,5-pentanediol, 2-ethyl-2-butylpropanediol, 1,9-nonanediol, 2-methyloctanediol, 1,10-decanediol, and derivatives thereof. The polyhydric alcohol monomers can be used alone or in combination of two or more kinds.

[0050] The polymer of the present embodiment may also include an ionic polymer. The ionic polymer is a polymer having an ionic functional group. When the polymer includes an ionic polymer, the relative dielectric constant of the polymer increases, and the electrical peeling property is improved. When the polymer includes an ionic polymer, the content of the ionic polymer is preferably 0.05 parts by mass or more and 2 parts by mass or less with respect to 100 parts by mass of the polymer.

[0051] In this embodiment, the polymer can be obtained by (co)polymerizing the monomer components. The polymerization method is not particularly limited, but includes solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, photopolymerization (active energy ray polymerization), and the like. In particular, from the viewpoint of cost and productivity, the solution polymerization method is preferable. When the polymer is copolymerized, it may be any of a random copolymer, a block copolymer, an alternating copolymer, a graft copolymer, and the like.

[0052] The solution polymerization method is not particularly limited, but examples thereof include a method in which a monomer component, a polymerization initiator, and the like are dissolved in a solvent and polymerized by heating to obtain a polymer solution containing a polymer.

[0053] As the solvent used in the solution polymerization method, various common solvents can be used. Examples of such solvents (polymerization solvents) include organic solvents such as aromatic hydrocarbons such as toluene, benzene, and xylene; esters such as ethyl acetate and n-butyl acetate; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone and methyl isobutyl ketone. The solvents can be used alone or in combination of two or more kinds.

[0054] The amount of the solvent used is not particularly limited, but is preferably 10 parts by mass or more and 1000 parts by mass or less based on the total monomer components (100 parts by mass) constituting the polymer. The upper limit of the amount of the solvent used is more preferably 500 parts by mass, and the lower limit is more preferably 50 parts by mass.

[0055] The polymerization initiator used in the solution polymerization method is not particularly limited, but includes peroxide-based polymerization initiators, azo-based polymerization initiators, etc. The peroxide-based polymerization initiator is not particularly limited, but includes peroxycarbonate, ketone peroxide, peroxyketal, hydroperoxide, dialkyl peroxide, diacyl peroxide, and peroxyester, and more specifically, includes benzoyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, t-butyl peroxybenzoate, dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-bis(t-butylperoxy)cyclododecane, etc. The azo polymerization initiator is not particularly limited, but may be 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionate)dimethyl, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4,4-trimethylpentane), 4,4'-azobis -4-cyanovaleric acid, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine) hydrochloride, and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate, etc. The polymerization initiator can be used alone or in combination of two or more kinds.

[0056] The amount of the polymerization initiator used is not particularly limited, but is preferably 0.01 parts by mass or more and 5 parts by mass or less based on the total monomer components (100 parts by mass) constituting the polymer. The upper limit of the amount of the polymerization initiator used is more preferably 3 parts by mass, and the lower limit is more preferably 0.05 parts by mass.

[0057] In the solution polymerization method, the heating temperature when polymerizing by heating is not particularly limited, but is, for example, 50° C. to 80° C. The heating time is not particularly limited, but is, for example, 1 hour to 24 hours.

[0058] The weight average molecular weight of the polymer is not particularly limited, but is preferably 100,000 or more and 5 million or less. The upper limit of the weight average molecular weight is more preferably 4 million, more preferably 3 million, and the lower limit is more preferably 200,000, more preferably 300,000. When the weight average molecular weight is 100,000 or more, the cohesive force is small, and the problem of adhesive residue on the adherend surface after peeling off the pressure-sensitive adhesive layer can be effectively suppressed. In addition, when the weight average molecular weight is 5 million or less, the problem of insufficient wettability on the adherend surface after peeling off the pressure-sensitive adhesive layer can be effectively suppressed.

[0059] The weight average molecular weight is obtained by measurement using a gel permeation chromatography (GPC) method, and more specifically, for example, it can be measured using a GPC measurement device (trade name "HLC-8220GPC" (manufactured by Tosoh Corporation) under the following conditions, and calculated in terms of standard polystyrene: (Weight average molecular weight measurement conditions) Sample concentration: 0.2% by mass (tetrahydrofuran solution) Sample injection volume: 10μL Sample column: TSKguardcolumn SuperHZ-H (1 column) + T SKgel SuperHZM-H (2 bottles) Reference column: TSKgel SuperH-RC (1 column) Eluent: Tetrahydrofuran (THF) ·Flow rate: 0.6mL / min Detector: Differential refractometer (RI) Column temperature (measurement temperature): 40℃

[0060] The glass transition temperature (Tg) of the polymer is not particularly limited, but is preferably 0° C. or lower since the decrease in the initial adhesive strength can be suppressed, more preferably −10° C. or lower, and even more preferably −20° C. or lower. Furthermore, it is particularly preferable that the glass transition temperature (Tg) be −40° C. or lower since the decrease rate of the adhesive strength due to the application of a voltage is particularly large, and is most preferably −50° C. or lower.

[0061] The glass transition temperature (Tg) can be calculated, for example, based on the following formula (Y) (Fox formula). 1 / Tg=W1 / Tg1+W2 / Tg2+···+Wn / Tgn (Y) [In formula (Y), Tg is the glass transition temperature of the polymer (unit: K), Tgi (i = 1, 2, ..., n) is the glass transition temperature (unit: K) when monomer i forms a homopolymer, and Wi (i = 1, 2, ..., n) is the mass fraction of monomer i in all monomer components] The above formula (Y) is a calculation formula when the polymer is composed of n types of monomer components, namely, monomer 1, monomer 2, . . . , monomer n.

[0062] The glass transition temperature when a homopolymer is formed means the glass transition temperature of a homopolymer of the monomer, and means the glass transition temperature (Tg) of a polymer formed using only a certain monomer (sometimes referred to as "monomer X") as a monomer component. Specifically, numerical values ​​are given in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989). The glass transition temperature (Tg) of a homopolymer not described in the document refers to a value obtained, for example, by the following measurement method. That is, 100 parts by mass of monomer X, 0.2 parts by mass of 2,2'-azobisisobutyronitrile, and 200 parts by mass of ethyl acetate as a polymerization solvent are put into a reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser tube, and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, the temperature is raised to 63°C and reacted for 10 hours. Then, the mixture is cooled to room temperature to obtain a homopolymer solution with a solid content concentration of 33% by mass. Next, the homopolymer solution is cast onto a release liner and dried to prepare a test sample (homopolymer sheet) with a thickness of about 2 mm. Then, about 1 to 2 mg of this test sample is weighed into an aluminum open cell, and the reversing heat flow (specific heat component) behavior of the homopolymer is obtained using a temperature-modulated DSC (trade name "Q-2000" manufactured by TA Instruments) at a heating rate of 5°C / min under a nitrogen atmosphere of 50 ml / min. With reference to JIS-K-7121, the glass transition temperature (Tg) of the homopolymer is determined as the temperature at the point where a straight line equidistant in the vertical direction from a straight line extending the low-temperature side baseline and the high-temperature side baseline of the obtained reversing heat flow intersects with the curve of the stepwise change part of the glass transition.

[0063] The polymer content in the pressure-sensitive adhesive composition of this embodiment is preferably 50 mass% or more and 99.9 mass% or less, relative to the total amount of the pressure-sensitive adhesive composition (100 mass%), with the upper limit being more preferably 99.5 mass%, and even more preferably 99 mass%, and the lower limit being more preferably 60 mass%, and even more preferably 70 mass%.

[0064] (Ionic Liquid) The ionic liquid in this embodiment is not particularly limited as long as it is a molten salt (room temperature molten salt) composed of a pair of anion and cation and is liquid at 25° C. Examples of anions and cations are given below, but among the ionic substances obtained by combining these, those that are liquid at 25° C. are ionic liquids, and those that are solid at 25° C. are not ionic liquids but ionic solids described below.

[0065] The anion of the ionic liquid is, for example, (FSO 2 ) 2 N - , (CF 3 SO 2 ) 2 N - , (CF 3 CF 2 SO 2 ) 2 N - , (CF 3 SO 2 ) 3 C - , Br - , AlCl 4 - , Al 2 Cl 7 - , NO 3 - , B.F. 4 - , P.F. 6 - , C.H. 3 COO - , C.F. 3 COO - , C.F. 3 CF 2 CF 2 COO - , C.F. 3 SO 3 - , C.F. 3 (CF 2 ) 3 SO 3 - , AsF 6 - , SbF 6 - , and F(HF) n -Among them, the anions are (FSO 2 ) 2 N - [bis(fluorosulfonyl)imide anion], and (CF 3 SO 2 ) 2 N - Anions of sulfonylimide compounds such as [bis(trifluoromethanesulfonyl)imide anion] are preferred because they are chemically stable and suitable for improving electrical peeling properties.

[0066] As the cation in the ionic liquid, nitrogen-containing onium, sulfur-containing onium, and phosphorus-containing onium cations are preferred because they are chemically stable and suitable for improving electrical peeling properties, and imidazolium-based, ammonium-based, pyrrolidinium-based, and pyridinium-based cations are more preferred.

[0067] Examples of imidazolium cations include 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-propyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-pentyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-heptyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-nonyl-3-methylimidazolium cation, 1-undecyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, imidazolium cation, 1-tridecyl-3-methylimidazolium cation, 1-tetradecyl-3-methylimidazolium cation, 1-pentadecyl-3-methylimidazolium cation, 1-hexadecyl-3-methylimidazolium cation, 1-heptadecyl-3-methylimidazolium cation, 1-octadecyl-3-methylimidazolium cation, 1-undecyl-3-methylimidazolium cation, 1-benzyl-3-methylimidazolium cation, 1-butyl-2,3-dimethylimidazolium cation, and 1,3-bis(dodecyl)imidazolium cation.

[0068] Examples of pyridinium cations include 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, and 1-octyl-4-methylpyridinium cation.

[0069] Examples of pyrrolidinium cations include 1-ethyl-1-methylpyrrolidinium cation and 1-butyl-1-methylpyrrolidinium cation.

[0070] Examples of ammonium-based cations include tetraethylammonium cation, tetrabutylammonium cation, methyltrioctylammonium cation, tetradecitrihexylammonium cation, glycidyltrimethylammonium cation, and trimethylaminoethyl acrylate cation.

[0071] From the viewpoint of increasing the rate of decrease in adhesive strength when a voltage is applied, it is preferable to select a cation having a molecular weight of 160 or less as the constituent cation of the ionic liquid. 2 ) 2 N - [Bis(fluorosulfonyl)imide anion] or (CF 3 SO 2 ) 2 N -Particularly preferred is an ionic liquid containing a [bis(trifluoromethanesulfonyl)imide anion] and a cation having a molecular weight of 160 or less. Examples of the cation having a molecular weight of 160 or less include 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-propyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-pentyl-3-methylimidazolium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, 1-ethyl-1-methylpyrrolidinium cation, 1-butyl-1-methylpyrrolidinium cation, tetraethylammonium cation, glycidyltrimethylammonium cation, and trimethylaminoethyl acrylate cation.

[0072] As the cation of the ionic liquid, the cations represented by the following formulas (2-A) to (2-D) are also preferred. [ka]

[0073] R in formula (2-A) 1 represents a hydrocarbon group having 4 to 10 carbon atoms (preferably a hydrocarbon group having 4 to 8 carbon atoms, more preferably a hydrocarbon group having 4 to 6 carbon atoms), which may contain a heteroatom; R 2 and R 3 are the same or different and each represents a hydrogen atom or a hydrocarbon group having 1 to 12 carbon atoms (preferably a hydrocarbon group having 1 to 8 carbon atoms, more preferably a hydrocarbon group having 2 to 6 carbon atoms, and further preferably a hydrocarbon group having 2 to 4 carbon atoms), and may contain a heteroatom. However, when a nitrogen atom forms a double bond with an adjacent carbon atom, R 3 does not exist.

[0074] R in formula (2-B) 4 represents a hydrocarbon group having 2 to 10 carbon atoms (preferably a hydrocarbon group having 2 to 8 carbon atoms, more preferably a hydrocarbon group having 2 to 6 carbon atoms), which may contain a heteroatom; R5 , R 6 , and R 7 are the same or different and represent a hydrogen atom or a hydrocarbon group having 1 to 12 carbon atoms (preferably a hydrocarbon group having 1 to 8 carbon atoms, more preferably a hydrocarbon group having 2 to 6 carbon atoms, and even more preferably a hydrocarbon group having 2 to 4 carbon atoms), which may contain a heteroatom.

[0075] R in formula (2-C) 8 represents a hydrocarbon group having 2 to 10 carbon atoms (preferably a hydrocarbon group having 2 to 8 carbon atoms, more preferably a hydrocarbon group having 2 to 6 carbon atoms), which may contain a heteroatom; R 9 , R 10 , and R 11 are the same or different and represent a hydrogen atom or a hydrocarbon group having 1 to 16 carbon atoms (preferably a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrocarbon group having 1 to 8 carbon atoms), which may contain a heteroatom.

[0076] In formula (2-D), X represents a nitrogen, sulfur, or phosphorus atom; R 12 , R 13 , R 14 , and R 15 are the same or different and each represents a hydrocarbon group having 1 to 16 carbon atoms (preferably a hydrocarbon group having 1 to 14 carbon atoms, more preferably a hydrocarbon group having 1 to 10 carbon atoms, further preferably a hydrocarbon group having 1 to 8 carbon atoms, and particularly preferably a hydrocarbon group having 1 to 6 carbon atoms), which may contain a heteroatom. However, when X is a sulfur atom, R 12 does not exist.

[0077] The molecular weight of the cation in the ionic liquid is, for example, 500 or less, preferably 400 or less, more preferably 300 or less, even more preferably 250 or less, particularly preferably 200 or less, and most preferably 160 or less. It is usually 50 or more. It is considered that the cation in the ionic liquid has a property of moving to the cathode side in the pressure-sensitive adhesive layer when a voltage is applied, and being biased toward the interface between the pressure-sensitive adhesive layer and the adherend. For this reason, in the present invention, the adhesive strength during voltage application decreases compared to the initial adhesive strength, and electrical peeling occurs. A cation having a small molecular weight, such as a molecular weight of 500 or less, is suitable for making it easier for the cation to move to the cathode side in the pressure-sensitive adhesive layer, and for increasing the rate of decrease in adhesive strength when a voltage is applied.

[0078] Examples of commercially available ionic liquids include "ELEXCEL AS-110", "ELEXCEL MP-442", "ELEXCEL IL-210", "ELEXCEL MP-471", "ELEXCEL MP-456", and "ELEXCEL AS-804" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., "HMI-FSI" manufactured by Mitsubishi Materials Corporation, and "CIL-312" and "CIL-313" manufactured by Nippon Carlit Co., Ltd.

[0079] The ionic conductivity of the ionic liquid is preferably 0.1 mS / cm or more and 10 mS / cm or less. The upper limit of the ionic conductivity is more preferably 5 mS / cm, more preferably 3 mS / cm, and the lower limit is more preferably 0.3 mS / cm, more preferably 0.5 mS / cm. By having an ionic conductivity in this range, the adhesive force is sufficiently reduced even at a low voltage. The ionic conductivity can be measured by an AC impedance method using, for example, a Solartron 1260 frequency response analyzer.

[0080] The content (mixture amount) of the ionic liquid in the adhesive composition of the present embodiment is preferably 0.5 parts by mass or more relative to 100 parts by mass of the polymer in terms of reducing the adhesive strength during voltage application, and is preferably 30 parts by mass or less in terms of increasing the initial adhesive strength. From the same viewpoint, it is more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, particularly preferably 10 parts by mass or less, and most preferably 5 parts by mass or less. Also, it is more preferably 0.6 parts by mass or more, even more preferably 0.8 parts by mass or more, particularly preferably 1.0 parts by mass or more, and most preferably 1.5 parts by mass or more.

[0081] (Other Ingredients) The pressure-sensitive adhesive composition of the present embodiment may contain one or more components other than the polymer and the ionic liquid (hereinafter, sometimes referred to as "other components") as necessary within a range that does not impair the effects of the present invention. Hereinafter, the other components that may be contained in the pressure-sensitive adhesive composition of the present embodiment will be described.

[0082] The pressure-sensitive adhesive composition of the present embodiment may contain an ionic additive for the purpose of controlling the relative dielectric constant, ionic conductivity, and capacitance. As the ionic additive, for example, an ionic solid can be used.

[0083] The ionic solid is an ionic substance that is solid at 25°C. The ionic solid is not particularly limited, but for example, a solid ionic substance obtained by combining an anion and a cation exemplified in the above-mentioned section on ionic liquids can be used. When the adhesive composition contains an ionic solid, the content of the ionic solid is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 2.5 parts by mass or less, relative to 100 parts by mass of the polymer.

[0084] The adhesive composition of the present embodiment may contain a crosslinking agent as necessary for the purpose of improving creep properties and shear properties by crosslinking the polymer. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, and amine-based crosslinking agents. Examples of the isocyanate-based crosslinking agent include toluene diisocyanate and methylene bisphenyl isocyanate. Examples of the epoxy-based crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylene diamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, and 1,6-hexanediol diglycidyl ether. When a crosslinking agent is contained, the content is preferably 0.1 parts by mass or more, more preferably 0.7 parts by mass or more, and is preferably 50 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 3 parts by mass or less, relative to 100 parts by mass of the polymer. The crosslinking agent may be used alone or in combination of two or more kinds.

[0085] The pressure-sensitive adhesive composition of the present embodiment may contain polyethylene glycol or tetraethylene glycol dimethyl ether as necessary for the purpose of aiding the movement of the ionic liquid when a voltage is applied. As the polyethylene glycol or tetraethylene glycol dimethyl ether, those having a number average molecular weight of 100 to 6000 can be used. When these components are contained, the content is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, and is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, relative to 100 parts by mass of the polymer.

[0086] The adhesive composition of the present embodiment may contain a conductive filler as necessary for the purpose of imparting electrical conductivity to the adhesive composition. The conductive filler is not particularly limited, and a commonly known or commonly used conductive filler can be used, for example, graphite, carbon black, carbon fiber, metal powder such as silver or copper, etc. When the conductive filler is contained, the content is preferably 0.1 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of the polymer.

[0087] The pressure-sensitive adhesive composition of the present embodiment may contain a corrosion inhibitor as necessary for the purpose of suppressing corrosion of the metal adherend. The corrosion inhibitor is not particularly limited, and a generally known or commonly used corrosion inhibitor can be used, such as a carbodiimide compound, an adsorptive inhibitor, or a chelating metal deactivator. Examples of the carbodiimide compound include 1-[3-(dimethylamino)propyl]-3-ethylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, N,N'-dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide, 1-ethyl-3-tert-butylcarbodiimide, N-cyclohexyl-N'-(2-morpholinoethyl)carbodiimide, N,N'-di-tert-butylcarbodiimide, 1,3-bis(p-tolyl)carbodiimide, and polycarbodiimide resins having these as monomers. These carbodiimide compounds can be used alone or in combination of two or more. When the pressure-sensitive adhesive composition of the present embodiment contains a carbodiimide compound, the content is preferably 0.01 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the polymer. Examples of the adsorptive inhibitor include alkylamines, carboxylates, carboxylate derivatives, and alkyl phosphates. The adsorptive inhibitors can be used alone or in combination of two or more. When the adhesive composition of the present embodiment contains an alkylamine as an adsorptive inhibitor, the content is preferably 0.01 to 20 parts by mass relative to 100 parts by mass of the polymer. When the adhesive composition of the present embodiment contains a carboxylate as an adsorptive inhibitor, the content is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the polymer. When the adhesive composition of the present embodiment contains a carboxylate as an adsorptive inhibitor, the content is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the polymer. When the adhesive composition of the present embodiment contains a carboxylate as an adsorptive inhibitor, the content is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the polymer. When the adhesive composition of the present embodiment contains an alkyl phosphate as an adsorptive inhibitor, the content is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the polymer. As the chelating metal deactivator, for example, a triazole group-containing compound or a benzotriazole group-containing compound can be used. These are preferred because they have a high effect of deactivating the surface of metals such as aluminum, and are less likely to affect adhesion even when contained in the adhesive component. The chelating metal deactivator can be used alone or in combination of two or more kinds. When the chelating metal deactivator is contained in the adhesive composition of the present embodiment, the content is preferably 0.01 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the polymer. The total content (blended amount) of the corrosion inhibitor is preferably 0.01 parts by mass or more and 30 parts by mass or less based on 100 parts by mass of the polymer.

[0088] The pressure-sensitive adhesive composition of the present embodiment may further contain various additives such as a filler, a plasticizer, an antiaging agent, an antioxidant, a pigment (dye), a flame retardant, a solvent, a surfactant (leveling agent), an antirust agent, an adhesion-imparting resin, and an antistatic agent. The total content of these components is not particularly limited as long as the effects of the present invention are exhibited, but is preferably 0.01 parts by mass or more and 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the polymer.

[0089] Examples of the filler include silica, iron oxide, zinc oxide, aluminum oxide, titanium oxide, barium oxide, magnesium oxide, calcium carbonate, magnesium carbonate, zinc carbonate, pyrophyllite clay, kaolin clay, and calcined clay. The plasticizer may be a known, commonly used plasticizer used in general resin compositions, etc., and examples of the plasticizer that may be used include oils such as paraffin oil and process oil, liquid rubbers such as liquid polyisoprene, liquid polybutadiene, and liquid ethylene-propylene rubber, tetrahydrophthalic acid, azelaic acid, benzoic acid, phthalic acid, trimellitic acid, pyromellitic acid, adipic acid, sebacic acid, fumaric acid, maleic acid, itaconic acid, citric acid, and derivatives thereof, dioctyl phthalate (DOP), dibutyl phthalate (DBP), dioctyl adipate, diisononyl adipate (DINA), and isodecyl succinate. Examples of the antioxidant include hindered phenol compounds, and aliphatic and aromatic hindered amine compounds. Examples of the antioxidant include butylhydroxytoluene (BHT) and butylhydroxyanisole (BHA). Examples of pigments include inorganic pigments such as titanium dioxide, zinc oxide, ultramarine, red iron oxide, lithopone, lead, cadmium, iron, cobalt, aluminum, hydrochlorides, and sulfates; azo pigments; and organic pigments such as copper phthalocyanine pigments. Examples of the rust inhibitor include zinc phosphate, tannic acid derivatives, phosphoric esters, basic sulfonates, and various rust inhibitor pigments. Examples of adhesion promoters include titanium coupling agents and zirconium coupling agents. As the antistatic agent, generally, a quaternary ammonium salt or a hydrophilic compound such as polyglycolic acid or an ethylene oxide derivative can be mentioned. Examples of tackifier resins include rosin-based tackifier resins, terpene-based tackifier resins, phenol-based tackifier resins, hydrocarbon-based tackifier resins, ketone-based tackifier resins, polyamide-based tackifier resins, epoxy-based tackifier resins, and elastomer-based tackifier resins, etc. The tackifier resins may be used alone or in combination of two or more kinds.

[0090] <Dielectric constant of pressure-sensitive adhesive layer not containing ionic liquid> In the adhesive composition of the first embodiment, an adhesive layer (ionic liquid-free adhesive layer) is formed from a composition (ionic liquid-free adhesive composition) consisting of components other than the ionic liquid among the components contained in the adhesive composition, and after leaving the adhesive layer for 3 days in an environment of 22°C and 20% RH, the adhesive layer has a relative dielectric constant of 5 or more at a frequency of 100 Hz.

[0091] The above-mentioned relative dielectric constant refers to a relative dielectric constant measured as follows. First, the ionic liquid-free adhesive composition is uniformly applied onto the release surface of a separator whose surface has been subjected to a release treatment, and then heated and dried at 130°C for 3 minutes to obtain an ionic liquid-free adhesive layer having a thickness of 30 μm. Next, the obtained ionic liquid-free adhesive layer is left in an environment of 22°C and 20% RH for 3 days. Thereafter, the relative dielectric constant is measured under the following conditions. (Conditions for measuring dielectric constant) Measurement method: Volumetric method (equipment: Agilent Technologies 4294A (Using Precision Impedance Analyzer) Electrode structure: 12.1mmΦ, 0.5mm thick aluminum plate Counter electrode: 60 μm thick aluminum foil Measurement environment: 23±1℃, 52±1%RH

[0092] The relative dielectric constant of the ionic liquid-free pressure-sensitive adhesive layer correlates with the ease of movement of the ionic liquid in the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition containing the ionic liquid. The greater the relative dielectric constant of the ionic liquid-free pressure-sensitive adhesive layer, the more easily the ionic liquid moves in the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition containing the ionic liquid, and therefore the more likely the adhesive strength is to decrease when a voltage is applied. The adhesive composition of the first embodiment has a dielectric constant of 5 or more at a frequency of 100 Hz after the ionic liquid-free adhesive layer is left in an environment of 22°C and 20% RH for 3 days, and therefore is capable of forming an adhesion whose adhesive strength is sufficiently reduced by application of voltage even in a low humidity environment.

[0093] The relative dielectric constant of the ionic liquid-free pressure-sensitive adhesive layer can be controlled, for example, by appropriately adjusting the polymer components in the pressure-sensitive adhesive composition and the type and content of the ionic additive within the above-mentioned suitable ranges.

[0094] <Ionic conductivity of the adhesive layer and capacitance per unit area of ​​the interface between the adhesive layer and the adherend> The pressure-sensitive adhesive composition of the second embodiment is a pressure-sensitive adhesive composition having a capacitance per unit area of ​​0.9 μF / cm per unit area at the interface between the pressure-sensitive adhesive layer and the aluminum plate after forming a pressure-sensitive adhesive layer from the pressure-sensitive adhesive composition, attaching the pressure-sensitive adhesive layer to an aluminum plate made of A5052P H32 according to JIS H4000:2014, and leaving the plate in an environment of 22° C. and 15% RH for 7 days. 2 The pressure-sensitive adhesive layer has an ionic conductivity of 10 μS / m or more.

[0095] The ionic conductivity of the adhesive layer correlates with the ease of movement of the ionic liquid in the adhesive layer, and the higher the ionic conductivity, the easier the ionic liquid moves. Also, the capacitance per unit area of ​​the interface between the adhesive layer and the adherend correlates with the ease of presence of the ionic liquid at the interface between the adhesive layer and the adherend, and the higher the capacitance, the easier it is for a large amount of ionic liquid to be present at the interface between the adhesive layer and the adherend. The pressure-sensitive adhesive composition of the second embodiment is a pressure-sensitive adhesive composition having a capacitance per unit area of ​​0.9 μF / cm per unit area at the interface between the pressure-sensitive adhesive layer and the aluminum plate after forming a pressure-sensitive adhesive layer from the pressure-sensitive adhesive composition, attaching the pressure-sensitive adhesive layer to an aluminum plate made of A5052P H32 according to JIS H4000:2014, and leaving the plate in an environment of 22° C. and 15% RH for 7 days. 2 Since the ionic conductivity of the pressure-sensitive adhesive layer is 10 μS / m or more, it is possible to form an adhesive in which the adhesive strength is sufficiently reduced by application of voltage even in a low humidity environment. 2 It is more preferable that the ionic conductivity of the pressure-sensitive adhesive layer is 20 μS / m or more.

[0096] The above ionic conductivity and capacitance can be controlled, for example, by appropriately adjusting the polymer components in the pressure-sensitive adhesive composition, the type and content of the ionic liquid, and the type and content of the ionic additive within the suitable ranges described above.

[0097] The above-mentioned ionic conductivity and capacitance refer to the ionic conductivity and capacitance measured as follows.

[0098] (Production of measurement samples (composite samples)) First, the adhesive composition is uniformly applied to the aluminum-deposited surface of an aluminum-deposited PET film 100 (product name "Metal Me TS" manufactured by Toray Advanced Film Co., Ltd.). At this time, in order to bring an electrode into contact with the aluminum-deposited surface, a portion is provided where the adhesive composition is not applied. Next, the adhesive layer 200 is formed by heating and drying at 130°C for 3 minutes, and an adhesive sheet sample is obtained. Thereafter, the adhesive surface of the obtained adhesive sheet sample is attached to an aluminum plate 300 (A5052P H32 (JIS H4000:2014)) to obtain a joint sample 400 having a shape as shown in Figs. 5 and 6. Fig. 5 is a side view, and Fig. 6 is a top view.

[0099] (Capacitance and ionic conductivity measurements) The capacitance and ionic conductivity are measured using an LCR meter (for example, IM3533 manufactured by Hioki E.E. Corporation). First, an AC voltage of 0.5 V is applied between the aluminum plate 300 and the aluminum-deposited surface of the aluminum-deposited PET film 100 using an LCR meter, and the frequency is changed from 0.5 Hz to 200 kHz to obtain a Cole-Cole plot.

[0100] Next, the bulk of the adhesive layer 200 is divided into resistance components R adh and the capacitance component C adh and the interface of the adhesive layer 200 is a resistance component R p and the capacitance component C dl The equivalent circuit of the bonded sample is set as shown in FIG. 7, and the obtained Cole-Cole plot is fitted by the following formula (A). 0 is the wiring resistance.

[0101]

number

[0102] In equation (A), ω is the angular frequency.

[0103] The obtained C dl By dividing by the area A of the adhesive surface of the adhesive layer 200, the capacitance per unit area of ​​the interface between the adhesive layer 200 and the aluminum plate 300 can be obtained.

[0104] Next, the bulk resistance component R of the pressure-sensitive adhesive layer 200 calculated from the formula (A) adh Using this, the ionic conductivity σ of the pressure-sensitive adhesive layer can be calculated using the following formula (B).

[0105]

number

[0106] In the formula (B), l is the thickness of the adhesive layer, and A is the area of ​​the adhesive surface of the adhesive layer 200.

[0107] <Initial adhesive strength, adhesive strength decrease rate due to voltage application> The adhesive strength of the pressure-sensitive adhesive composition of this embodiment can be evaluated by various methods, for example, the 180° peel test described in the Examples section.

[0108] The pressure-sensitive adhesive composition of this embodiment is formed into a pressure-sensitive adhesive sheet as described in the Examples section, and the initial adhesive strength measured by carrying out a 180° peel test is preferably 1.0 N / cm or more, more preferably 1.5 N / cm or more, even more preferably 2.0 N / cm or more, particularly preferably 2.5 N / cm or more, and most preferably 3.0 N / cm or more. If the initial adhesive strength is 1.0 N / cm or more, the adhesion to the adherend is sufficient, and the adherend is unlikely to peel off or shift.

[0109] Furthermore, the pressure-sensitive adhesive composition of the present embodiment is preferably prepared by forming a pressure-sensitive adhesive sheet as described in the Examples section, leaving the sheet for a predetermined period of time under an environment of predetermined temperature and humidity, applying a voltage of 10 V for 30 seconds, and then measuring the adhesive strength in a 180° peel test while applying a voltage of 10 V, which is sufficiently smaller than the initial adhesive strength. That is, the adhesive strength reduction rate calculated from the adhesive strength measured by the above method (simply referred to as "adhesive strength during voltage application" in the following formula (C)) and the initial adhesive strength by the following formula (C) is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. The above-mentioned specified temperature, humidity, and period are preferably 22°C and 20% RH for 3 days, and more preferably 22°C and 15% RH for 7 days. Adhesive strength decrease rate (%) = {1-(adhesive strength during voltage application / initial adhesive strength)} x 100 (C)

[0110] The applied voltage and voltage application time during electrical peeling are not limited to those mentioned above, and are not particularly limited as long as the pressure-sensitive adhesive sheet can be peeled off. Preferred ranges for these are shown below. The applied voltage is preferably 1 V or more, more preferably 3 V or more, and even more preferably 6 V or more. Also, it is preferably 100 V or less, more preferably 50 V or less, even more preferably 30 V or less, and particularly preferably 15 V or less. The voltage application time is preferably 60 seconds or less, more preferably 40 seconds or less, even more preferably 20 seconds or less, and particularly preferably 10 seconds or less. In such a case, the workability is excellent. In addition, the shorter the application time, the better, but it is usually 1 second or more.

[0111] <Method of producing pressure-sensitive adhesive composition> The pressure-sensitive adhesive composition of the present invention is not particularly limited, but can be produced by appropriately stirring and mixing a polymer, an ionic liquid, an additive, and, if necessary, a crosslinking agent, polyethylene glycol, a conductive filler, etc.

[0112] [Adhesive sheet] (Structure of adhesive sheet) The adhesive sheet of the present embodiment is not particularly limited as long as it has at least one adhesive layer (hereinafter also referred to as "electrically peelable adhesive layer") formed from the above-mentioned adhesive composition of the present embodiment. The adhesive sheet of the present embodiment may have an adhesive layer (hereinafter sometimes referred to as "other adhesive layer") that does not contain an ionic liquid other than the electrically peelable adhesive layer. The adhesive sheet of the present embodiment may have a substrate, a conductive layer, a conductive substrate, an intermediate layer, an undercoat layer, and the like in addition to the above. The adhesive sheet of the present embodiment may be in the form of, for example, a roll or a sheet. It should be noted that the term "adhesive sheet" also includes the meaning of "adhesive tape". That is, the adhesive sheet of the present embodiment may be an adhesive tape having a tape-like form.

[0113] The pressure-sensitive adhesive sheet of this embodiment may be a double-sided pressure-sensitive adhesive sheet that does not have a substrate and is composed only of an electrically peelable pressure-sensitive adhesive layer, i.e., does not include a substrate layer (substrate-less). The pressure-sensitive adhesive sheet of this embodiment may be a double-sided pressure-sensitive adhesive sheet that has a substrate, and both sides of the substrate are pressure-sensitive adhesive layers (electrically peelable pressure-sensitive adhesive layers or other pressure-sensitive adhesive layers). The pressure-sensitive adhesive sheet of this embodiment may be a single-sided pressure-sensitive adhesive sheet that has a substrate, and only one side of the substrate is a pressure-sensitive adhesive layer (electrically peelable pressure-sensitive adhesive layer or other pressure-sensitive adhesive layer). The pressure-sensitive adhesive sheet of this embodiment may have a separator (release liner) for the purpose of protecting the surface of the pressure-sensitive adhesive layer, but the separator is not included in the pressure-sensitive adhesive sheet of this embodiment.

[0114] The structure of the adhesive sheet of the present embodiment is not particularly limited, and preferred examples thereof include adhesive sheet X1 shown in FIG. 1, adhesive sheet X2 shown in FIG. 2, and adhesive sheet X3 shown in FIG. 3. Adhesive sheet X1 is a substrate-less double-sided adhesive sheet consisting of only an electrically peelable adhesive layer 1. Adhesive sheet X2 is a substrate-attached double-sided adhesive sheet having a layer structure of an adhesive layer 2, an electrically conductive substrate 5 (substrate 3 and conductive layer 4), and an electrically peelable adhesive layer 1. Adhesive sheet X3 is a substrate-attached double-sided adhesive sheet having a layer structure of an adhesive layer 2, an electrically conductive substrate 5 (substrate 3 and conductive layer 4), an electrically peelable adhesive layer 1, an electrically conductive substrate 5 (substrate 3 and conductive layer 4), and an adhesive layer 2. In the electrically conductive substrate 5 of adhesive sheets X2 and X3 shown in FIGS. 2 and 3, the substrate 3 is not essential, and only the conductive layer 4 may be present. In addition, the adhesive sheet X2 in FIG. 2 may be a single-sided adhesive sheet without the adhesive layer 2.

[0115] The substrate 3 is not particularly limited, but examples thereof include paper substrates such as paper, fiber substrates such as cloth and nonwoven fabric, plastic substrates such as films and sheets made of various plastics (polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate, acrylic resins such as polymethyl methacrylate, etc.), and laminates thereof. The substrate may have a single layer form or a multi-layer form. The substrate may be subjected to various treatments such as back surface treatment, antistatic treatment, and undercoat treatment, as necessary.

[0116] The conductive layer 4 is not particularly limited as long as it is a layer having conductivity, and may be a metal-based substrate such as a metal (e.g., aluminum, magnesium, copper, iron, tin, gold, etc.) foil, a metal plate (e.g., aluminum, magnesium, copper, iron, tin, silver, etc.), a conductive polymer, or the like, or may be a metal vapor deposition film provided on the substrate 3.

[0117] The conductive substrate 5 is not particularly limited as long as it is a substrate having a conductive layer (conductive), but examples thereof include a substrate having a metal layer formed on the surface thereof, such as the substrates exemplified above on which a metal layer is formed by plating, chemical vapor deposition, sputtering, etc. Examples of the metal layer include the metals, metal plates, conductive polymers, etc. exemplified above.

[0118] In the pressure-sensitive adhesive sheet X1, the adherends on both sides preferably have a metal adherend surface. In the pressure-sensitive adhesive sheet X2, the adherend on the electrically peelable pressure-sensitive adhesive layer 1 side preferably has a metal adherend surface.

[0119] Examples of the metal-coated surface include conductive surfaces made of metals such as aluminum, copper, iron, magnesium, tin, gold, silver, and lead, among which surfaces made of metals containing aluminum are preferred. Examples of the adherends having a metal-coated surface include sheets, parts, and plates made of metals such as aluminum, copper, iron, magnesium, tin, gold, silver, and lead. Adherends other than those having a metal-coated surface include, but are not limited to, fiber sheets such as paper, cloth, and nonwoven fabric, and various plastic films and sheets.

[0120] From the viewpoint of initial adhesive strength, the thickness of the electrically peelable pressure-sensitive adhesive layer 1 is preferably 1 μm or more and 1000 μm or less. The upper limit of the thickness of the electrically peelable pressure-sensitive adhesive layer 1 is more preferably 500 μm, even more preferably 100 μm, and particularly preferably 30 μm, and the lower limit is more preferably 3 μm, even more preferably 5 μm, and particularly preferably 8 μm. When the pressure-sensitive adhesive sheet is a substrate-less double-sided pressure-sensitive adhesive sheet consisting of only one electrically peelable pressure-sensitive adhesive layer (pressure-sensitive adhesive sheet X1 shown in FIG. 1), the thickness of the electrically peelable pressure-sensitive adhesive layer is the thickness of the pressure-sensitive adhesive sheet.

[0121] From the viewpoint of adhesive strength, the thickness of the pressure-sensitive adhesive layer 2 is preferably 1 μm or more and 2000 μm or less. The upper limit of the thickness of the pressure-sensitive adhesive layer 2 is more preferably 1000 μm, further preferably 500 μm, and particularly preferably 100 μm, and the lower limit is more preferably 3 μm, further preferably 5 μm, and particularly preferably 8 μm.

[0122] The thickness of the substrate 3 is preferably 10 μm or more and 1000 μm or less. The upper limit of the thickness is more preferably 500 μm, further preferably 300 μm, and particularly preferably 100 μm, and the lower limit is more preferably 12 μm, and further preferably 25 μm.

[0123] The thickness of the conductive layer 4 is preferably 0.001 μm or more and 1000 μm or less. The upper limit of the thickness is more preferably 500 μm, further preferably 300 μm, further preferably 50 μm, further preferably 10 μm, and the lower limit is more preferably 0.01 μm, more preferably 0.03 μm, further preferably 0.05 μm.

[0124] The thickness of the conductive substrate 5 is preferably 10 μm or more and 1000 μm or less. The upper limit of the thickness is more preferably 500 μm, further preferably 300 μm, and particularly preferably 100 μm, and the lower limit is more preferably 12 μm, and further preferably 25 μm.

[0125] The surface of the electrically peelable adhesive layer and other adhesive layers of the adhesive sheet of this embodiment may be protected by a separator (release liner). The separator is not particularly limited, but may be a release liner in which the surface of a substrate (liner substrate) such as paper or plastic film is silicone-treated, or a release liner in which the surface of a substrate (liner substrate) such as paper or plastic film is laminated with a polyolefin resin. The thickness of the separator is not particularly limited, but is preferably 10 μm or more and 100 μm or less.

[0126] The thickness of the pressure-sensitive adhesive sheet of this embodiment is preferably 20 μm or more and 3000 μm or less. The upper limit of the thickness is more preferably 1000 μm, even more preferably 300 μm, and particularly preferably 200 μm, and the lower limit is more preferably 30 μm, and even more preferably 50 μm.

[0127] In particular, in the case of the pressure-sensitive adhesive sheet X2 shown in Fig. 2, the thickness of the pressure-sensitive adhesive sheet is preferably 50 µm or more and 2000 µm or less. The upper limit of the thickness is more preferably 1000 µm, and even more preferably 200 µm, and the lower limit is more preferably 80 µm, and even more preferably 100 µm.

[0128] In particular, in the case of the adhesive sheet X3 shown in Fig. 3, the thickness of the adhesive sheet is preferably 100 µm or more and 3000 µm or less. The upper limit of the thickness is more preferably 1000 µm, and even more preferably 300 µm, and the lower limit is more preferably 150 µm, and even more preferably 200 µm.

[0129] (Method of manufacturing pressure-sensitive adhesive sheet) The adhesive sheet of this embodiment can be produced by a known or commonly used production method. The electrically peelable adhesive layer in the adhesive sheet of this embodiment can be produced by, for example, dissolving the adhesive composition of this embodiment in a solvent as needed, applying the solution onto a separator, followed by drying and / or curing. The other adhesive layers can be produced by, for example, dissolving the adhesive composition not containing ionic liquid and additives in a solvent as needed, applying the solution onto a separator, followed by drying and / or curing. The solvent and separator can be the same as those listed above.

[0130] For application, a conventional coater (for example, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, a spray roll coater, etc.) can be used.

[0131] The above method can produce an electrically peelable pressure-sensitive adhesive layer and other pressure-sensitive adhesive layers, and the pressure-sensitive adhesive sheet of the present embodiment can be produced by appropriately laminating the electrically peelable pressure-sensitive adhesive layer and other pressure-sensitive adhesive layers on a substrate, a conductive layer, and a conductive substrate. Note that the pressure-sensitive adhesive sheet may be produced by applying the pressure-sensitive adhesive composition to the substrate, a conductive layer, and a conductive substrate instead of a separator.

[0132] (Method of electrically peeling off adhesive sheets) The adhesive sheet of this embodiment can be peeled off from the adherend by applying a voltage to the electrically peelable adhesive layer to generate a potential difference in the thickness direction of the electrically peelable adhesive layer. For example, in the case of the adhesive sheet X1, when the adherend has a metal coating surface on both sides, the adhesive sheet can be peeled off by passing electricity through the metal coating surfaces on both sides and applying a voltage to the electrically peelable adhesive layer. In the case of the adhesive sheet X2, when the adherend has a metal coating surface on the electrically peelable adhesive layer side, the adhesive sheet can be peeled off by passing electricity through the conductive adherend and the conductive layer 4 and applying a voltage to the electrically peelable adhesive layer. In the case of the adhesive sheet X3, the adhesive sheet can be peeled off by passing electricity through the conductive layer 4 on both sides and applying a voltage to the electrically peelable adhesive layer. It is preferable to apply electricity by connecting terminals to one end and the other end of the adhesive sheet so that a voltage is applied to the entire electrically peelable adhesive layer. In addition, when the adherend has a metal coating surface, the one end and the other end may be a part of the adherend having a metal coating surface. During peeling, water may be added to the interface between the metal adherend surface and the electrically peelable pressure-sensitive adhesive layer before applying a voltage.

[0133] (Applications of adhesive sheets) Conventional peeling techniques include an adhesive layer that is hardened and peeled off by ultraviolet (UV) irradiation, and an adhesive layer that is peeled off by heat. Adhesive sheets using such adhesive layers cannot be used in cases where ultraviolet (UV) irradiation is difficult or where heat damages the adherend. The adhesive sheet of the present embodiment having the electrically peelable adhesive layer does not use ultraviolet or heat, so that it can be easily peeled off by applying a voltage without damaging the adherend. Therefore, the adhesive sheet of the present embodiment is suitable for use in fixing a secondary battery (e.g., a lithium-ion battery pack) used in a mobile terminal such as a smartphone, a mobile phone, a laptop computer, a video camera, or a digital camera to a housing.

[0134] In addition, examples of rigid members to be bonded by the adhesive sheet of this embodiment include silicon substrates for semiconductor wafers, sapphire substrates for LEDs, SiC substrates and metal-based substrates, TFT substrates and color filter substrates for displays, and base substrates for organic EL panels. Examples of fragile members to be bonded by the double-sided adhesive sheet include semiconductor substrates such as compound semiconductor substrates, silicon substrates for MEMS devices, passive matrix substrates, front cover glass for smartphones, OGS (One Glass Solution) substrates in which a touch panel sensor is attached to the cover glass, organic substrates and organic-inorganic hybrid substrates mainly composed of silsesquioxane, flexible glass substrates for flexible displays, and graphene sheets.

[0135] [zygote] The bonded body of the present embodiment has a laminated structure including an adherend having a metal adhesion surface and an adhesive sheet having an electrically peelable adhesive layer bonded to the metal adhesion surface. Examples of the adherend having a metal adhesion surface include those made of metals mainly composed of aluminum, copper, iron, magnesium, tin, gold, silver, lead, etc., and among these, metals containing aluminum are preferred.

[0136] Examples of the bonded body of this embodiment include a bonded body of adhesive sheet X1 having an adherend with a metal coating surface on both sides of electrically peelable adhesive layer 1, a bonded body of adhesive sheet X2 having an adherend with a metal coating surface on the electrically peelable adhesive layer 1 side and an adherend on the adhesive layer 2 side, a bonded body of adhesive sheet X3 having adherends on both sides of adhesive layer 2, etc. EXAMPLES

[0137] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The weight average molecular weights shown below were measured by the gel permeation chromatography (GPC) method described above.

[0138] [Examples 1-1 to 1-8, Comparative Examples 1-1 to 1-5] <Preparation of polymer solution> (Preparation of acrylic polymer 1 solution) As monomer components, n-butyl acrylate (BA): 95 parts by mass, acrylic acid (AA): 5 parts by mass, and ethyl acetate: 150 parts by mass as a polymerization solvent were charged into a separable flask, and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 2,2'-azobisisobutyronitrile (AIBN): 0.2 parts by mass was added as a polymerization initiator, and the temperature was raised to 63°C and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 1 solution with a solid content concentration of 40% by mass.

[0139] (Preparation of acrylic polymer 2 solution) As monomer components, n-butyl acrylate (BA): 90 parts by mass, 4-hydroxybutyl acrylate (4HBA): 10 parts by mass, and ethyl acetate: 150 parts by mass as a polymerization solvent were charged into a separable flask, and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 2,2'-azobisisobutyronitrile (AIBN): 0.2 parts by mass was added as a polymerization initiator, and the temperature was raised to 63°C and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 2 solution with a solid content concentration of 30% by mass.

[0140] (Preparation of acrylic polymer 3 solutions) As monomer components, 67 parts by mass of n-butyl acrylate (BA), 30 parts by mass of 2-methoxyethyl acrylate (MEA), 3 parts by mass of acrylic acid (AA), and 150 parts by mass of ethyl acetate as a polymerization solvent were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the mixture was heated to 63°C and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 3 solution with a solid content concentration of 40% by mass.

[0141] (Preparation of acrylic polymer 4 solution) As monomer components, 67 parts by mass of n-butyl acrylate (BA), 33 parts by mass of methyl methacrylate (MMA), and 150 parts by mass of ethyl acetate as a polymerization solvent were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the mixture was heated to 63°C and reacted for 6 hours. Ethyl acetate was then added to obtain an acrylic polymer 4 solution with a solid content concentration of 40% by mass.

[0142] (Preparation of acrylic polymer 5 solution) As monomer components, 87 parts by mass of n-butyl acrylate (BA), 10 parts by mass of 4-hydroxybutyl acrylate (4HBA), 3 parts by mass of acrylic acid (AA), and 150 parts by mass of ethyl acetate as a polymerization solvent were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the mixture was heated to 63°C and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 5 solution with a solid content concentration of 30% by mass.

[0143] <Preparation of Pressure-Sensitive Adhesive Composition> The acrylic polymer solution obtained above, the polymer, crosslinking agent, ionic liquid, and additives shown below were added and stirred and mixed to obtain pressure-sensitive adhesive compositions of Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-5. Table 1 shows the amount of each component. The values ​​of each component in Table 1 mean parts by mass. The blend amount (parts by mass) of the polymer indicates the blend amount (parts by mass) of the solid content in the polymer solution. The abbreviations for the polymer, crosslinker, ionic liquid, and additives in Table 1 are as follows. (polymer) Byron UR-V8700: Urethane modified polyester resin, product name "Byron UR-V8700", manufactured by Toyobo Co., Ltd. Byron BX1001: Polyester resin, product name "Byron BX1001", manufactured by Toyobo Co., Ltd. Somarex 530: Anionic polyacrylamide polymer (ionic polymer), product name "Somalex 530", manufactured by Somar Co., Ltd. (Ionic Liquid) AS-110: cation: 1-ethyl-3-methylimidazolium cation, anion: bis(fluorosulfonyl)imide anion, trade name "Elexel AS-110", manufactured by Daiichi Kogyo Seiyaku Co., Ltd. (Crosslinking agent) V-05: Polycarbodiimide resin, product name "Carbodilite V-05", manufactured by Nisshinbo Chemical Inc. Takenate D110: Trimethylolpropane xylylene diisocyanate, product name "Takenate D110N", manufactured by Mitsui Chemicals, Inc. (additive) EMI-nitrate: 1-ethyl-3-methylimidazolium nitrate, manufactured by Tokyo Chemical Industry Co., Ltd. Zn-nitrate: zinc nitrate hexahydrate, manufactured by Wako Pure Chemical Industries, Ltd. BTC-5B: Barium titanate No.27776: Carbon black

[0144] <Measurement of the relative dielectric constant of the pressure-sensitive adhesive layer not containing ionic liquid> The ionic liquid-free adhesive composition obtained by stirring and mixing the materials in the same manner as in the above Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-5, except that the ionic liquid was not added, was applied to a uniform thickness on the release-treated surface of a polyethylene terephthalate separator (product name "MRF38", manufactured by Mitsubishi Plastics, Inc.) whose surface had been subjected to a release treatment, using an applicator. Next, the composition was dried by heating at 130°C for 3 minutes to obtain an ionic liquid-free adhesive layer having a thickness of 30 μm. Next, the obtained ionic liquid-free adhesive layer was left for 3 days in an environment of 22°C and 20% RH, and then the relative dielectric constant of the adhesive layer at a frequency of 100 kHz was measured according to JIS K 6911 under the following conditions. (Measurement conditions) Measurement method: Volumetric method (equipment: Agilent Technologies 4294A (Using Precision Impedance Analyzer) Electrode structure: 12.1mmΦ, 0.5mm thick aluminum plate Counter electrode: 3oz copper plate Measurement environment: 23±1℃, 52±1%RH

[0145] <Measurement of moisture content of electrically peelable adhesive layer> The electrically peelable adhesive layer obtained in the same manner as above using the adhesive composition of each example was left for 3 days in an environment of 22°C and 20% RH, and the moisture content of the adhesive layer was measured by Karl Fischer moisture vaporization-coulometric titration method (JIS K 0113:2005). Specifically, the amount of moisture generated by heating and vaporizing at 200°C for 30 minutes was measured using a Hiranuma trace moisture analyzer AQ-2100 manufactured by Hiranuma Sangyo Co., Ltd., and the ratio to the weight of the sample before heating was taken as the moisture content. That is, the moisture content was calculated by the following formula. In Table 1, "-" means not measured. Moisture content (%) = (Karl Fischer measured moisture content / total weight of sample before measurement) x 100

[0146] <Evaluation> (Initial adhesive strength) The adhesive composition of each example was applied to a uniform thickness using an applicator onto the release-treated surface of a polyethylene terephthalate separator (product name "MRF38", manufactured by Mitsubishi Plastics, Inc.) whose surface had been subjected to a release treatment. Next, the applied composition was dried by heating at 130°C for 3 minutes to obtain an electrically peelable adhesive layer (adhesive sheet) having a thickness of 30 μm. Next, the obtained electrically peelable adhesive layer (adhesive sheet) was cut into a sheet of 10 mm x 80 mm in size, and the metal layer surface of a film with a metal layer (product name "BR1075", manufactured by Toray Film Processing Co., Ltd., thickness 25 μm, size 10 mm x 100 mm) was attached as a substrate to the surface without the separator to obtain a single-sided adhesive sheet with a substrate. The separator was peeled off from the single-sided adhesive sheet with substrate, and an aluminum plate (A5052P H32 (JIS H4000:2014)) was attached as an adherend to the peeled surface so that one end of the adhesive sheet protruded from the adherend by about 2 mm, and pressed once back and forth with a 2 kg roller and left in an environment of 23 ° C. for 30 minutes to obtain an assembly consisting of stainless steel plate 6 / electrically peelable adhesive layer (adhesive sheet) 1 ' / film with a metal layer (electrically conductive substrate) 5 '. An overview of the assembly is shown in FIG. 4. Thereafter, the adhesive strength was measured in a 180° peel test (tensile speed: 300 mm / min, peel temperature: 23° C.) by peeling in the direction of the arrow in FIG. 4 using a peel tester (product name "Variable Angle Peel Tester YSP", manufactured by Asahi Seiko Co., Ltd.). The measurement results are shown in Table 1.

[0147] (Adhesion strength when voltage is applied) The adhesive strength during voltage application was measured in the same manner as in the above initial adhesive strength measurement, except that after pressing once back and forth with a 2 kg roller, the bonded body was left to stand for 3 days in an environment of 22°C and 20% RH, and before peeling, the negative and positive electrodes of a DC machine were attached to the α and β points in Figure 4 of the bonded body, respectively, and a voltage of 10 V was applied for 30 seconds, and the bonded body was peeled while the voltage was still applied. The measurement results are shown in Table 1.

[0148] (Adhesive strength reduction rate) The initial adhesive strength and the adhesive strength during voltage application measured by the above method were used to calculate the adhesive strength reduction rate due to voltage application according to the following formula (C). The results are shown in Table 1. Adhesive strength decrease rate (%) = {1-(adhesive strength during voltage application / initial adhesive strength)} x 100 (C)

[0149] [Table 1]

[0150] An adhesive layer was formed using a composition consisting of components other than the ionic liquid among the components contained in the adhesive composition, and the adhesive layer was left to stand for 3 days in an environment of 22°C and 20% RH. After that, the adhesive compositions of Examples 1-1 to 1-8, in which the adhesive layer had a relative dielectric constant of 5 or more at a frequency of 100 Hz, all showed a large rate of adhesive strength loss due to voltage application.

[0151] [Examples 2-1 to 2-11, Comparative Examples 2-1 to 2-3] <Preparation of polymer solution> (Preparation of acrylic polymer 6 solution) As monomer components, 90 parts by mass of n-butyl acrylate (BA), 10 parts by mass of acrylic acid (AA), and 150 parts by mass of ethyl acetate as a polymerization solvent were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the mixture was heated to 63°C and reacted for 6 hours. Ethyl acetate was then added to obtain an acrylic polymer 6 solution with a solid content concentration of 40% by mass.

[0152] (Preparation of acrylic polymer 7 solution) As monomer components, n-butyl acrylate (BA): 90 parts by mass, 4-hydroxybutyl acrylate (4HBA): 7 parts by mass, acrylic acid (AA): 3 parts by mass, and ethyl acetate: 150 parts by mass as a polymerization solvent were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 2,2'-azobisisobutyronitrile (AIBN): 0.2 parts by mass was added as a polymerization initiator, and the temperature was raised to 63°C and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 7 solution with a solid content concentration of 30% by mass.

[0153] (Preparation of acrylic polymer 8 solution) As monomer components, n-butyl acrylate (BA): 94 parts by mass, 4-hydroxybutyl acrylate (4HBA): 3 parts by mass, acrylic acid (AA): 3 parts by mass, and ethyl acetate: 150 parts by mass as a polymerization solvent were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 2,2'-azobisisobutyronitrile (AIBN): 0.2 parts by mass was added as a polymerization initiator, and the temperature was raised to 63°C and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 8 solution with a solid content concentration of 30% by mass.

[0154] (Preparation of acrylic polymer 9 solution) As monomer components, n-butyl acrylate (BA): 77 parts by mass, 2-methoxyethyl acrylate (MEA): 20 parts by mass, acrylic acid (AA): 3 parts by mass, and ethyl acetate: 150 parts by mass as a polymerization solvent were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 2,2'-azobisisobutyronitrile (AIBN): 0.2 parts by mass was added as a polymerization initiator, and the temperature was raised to 63 ° C. and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 9 solution with a solid content concentration of 40 mass%.

[0155] (Preparation of acrylic polymer 10 solutions) As monomer components, 87 parts by mass of n-butyl acrylate (BA), 10 parts by mass of 2-methoxyethyl acrylate (MEA), 3 parts by mass of acrylic acid (AA), and 150 parts by mass of ethyl acetate as a polymerization solvent were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the mixture was heated to 63°C and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 10 solution with a solid content concentration of 40% by mass.

[0156] <Preparation of Pressure-Sensitive Adhesive Composition> The acrylic polymer solution obtained above, the above-mentioned polymer, crosslinking agent, ionic liquid, additive, or the following ionic liquid and corrosion inhibitor were added and stirred to obtain pressure-sensitive adhesive compositions of Examples 2-1 to 2-11 and Comparative Examples 2-1 to 2-3. Table 2 shows the amount of each component. (Ionic Liquid) 1-Hexyl-pyridinium-bis(trifluorosulfonyl)imide (corrosion inhibitors, additives, crosslinking agents) Irgamet30: N,N-bis(2-ethylhexyl)-1,2,4-triazol-1-ylmethanamine, trade name "Irgamet30", manufactured by BASF IrgacorDSSG: Disodium sebacate, product name "IrgametDSSG", manufactured by BASF AminO: Imidazoline derivative, product name "Amin O", manufactured by BASF PEG400: Polyethylene glycol, product name "PEG400", manufactured by Tokyo Chemical Industry Co., Ltd. Coronate L: Isocyanate compound, product name "Coronate L", manufactured by Tosoh Corporation

[0157] <Measurement of ionic conductivity and capacitance per unit area of ​​adhesive layer> Using the pressure-sensitive adhesive composition of each example, a measurement sample (composite sample) was prepared as follows, and the capacitance of the adhesive interface and the ionic conductivity of the pressure-sensitive adhesive layer were determined by the following methods. The results are shown in Table 2.

[0158] (Production of measurement samples (composite samples)) First, the adhesive composition was uniformly applied to the aluminum-deposited surface of an aluminum-deposited PET film 100 (product name "Metal Me TS" manufactured by Toray Advanced Film Co., Ltd.). At this time, in order to bring an electrode into contact with the aluminum-deposited surface, a portion was provided where the adhesive composition was not applied. Next, the adhesive layer 200 was formed by heating and drying at 130°C for 3 minutes, and an adhesive sheet sample was obtained. Thereafter, the adhesive surface of the obtained adhesive sheet sample was attached to an aluminum plate 300 (A5052P H32 (JIS H4000:2014)), and a joint sample 400 having a shape as shown in Figs. 5 and 6 was obtained. Fig. 5 is a side view, and Fig. 6 is a top view.

[0159] (Capacitance and ionic conductivity measurements) The capacitance and ionic conductivity were measured using an LCR meter (for example, IM3533 manufactured by Hioki E.E. Corporation). First, an AC voltage of 0.5 V was applied between the aluminum plate 300 and the aluminum-deposited surface of the aluminum-deposited PET film 100 using an LCR meter, and the frequency was changed from 0.5 Hz to 200 kHz to obtain a Cole-Cole plot.

[0160] Next, the bulk of the adhesive layer 200 is divided into resistance components R adh and the capacitance component C adh and the interface of the adhesive layer 200 is a resistance component R p and the capacitance component C dl The equivalent circuit of the bonded sample was set as shown in FIG. 7, and the obtained Cole-Cole plot was fitted by the following formula (A). 0 is the wiring resistance.

number

[0161] In equation (A), ω is the angular frequency.

[0162] The obtained C dlBy dividing by the area A of the adhesive surface of the adhesive layer 200, the capacitance per unit area of ​​the interface between the adhesive layer 200 and the aluminum plate 300 was calculated.

[0163] Next, the bulk resistance component R of the pressure-sensitive adhesive layer 200 calculated from the formula (A) adh The ionic conductivity σ of the pressure-sensitive adhesive layer was calculated using the following formula (B).

[0164]

number

[0165] In the formula (B), l is the thickness of the adhesive layer, and A is the area of ​​the adhesive surface of the adhesive layer 200.

[0166] <Evaluation> (Initial adhesive strength) For the pressure-sensitive adhesive composition of each example, an aluminum-deposited PET film (product name "Metal Me TS" manufactured by Toray Advanced Film Co., Ltd.) was used as the substrate, and a pressure-sensitive adhesive layer was formed on the aluminum-deposited surface, and the initial adhesive strength was measured in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-5. The measurement results are shown in Table 2.

[0167] (Adhesive strength during voltage application after storage for 3 days at 22°C and 20% RH) The adhesive strength during voltage application was measured in the same manner as in the above initial adhesive strength measurement, except that after pressing once with a 2 kg roller, the bonded body was left to stand for 3 days in an environment of 22°C and 20% RH, and before peeling, the negative and positive electrodes of a DC current machine were attached to the α and β points in Figure 4 of the bonded body, respectively, and a voltage of 10 V was applied for 30 seconds and then peeled while the voltage was still applied. The electrical peelability was evaluated according to the following criteria. The measurement results are shown in Table 2. ○: Adhesive strength reduction rate is 60% or more. ×: The adhesive strength reduction rate is less than 60%.

[0168] (Adhesive strength during voltage application after storage for 7 days at 22°C and 15% RH) The adhesive strength during voltage application was measured in the same manner as in the above initial adhesive strength measurement, except that after pressing once back and forth with a 2 kg roller, the bonded body was left to stand for 7 days in an environment of 22°C and 15% RH, and before peeling, the negative and positive electrodes of a DC current machine were attached to the α and β points in Figure 4 of the bonded body, respectively, and a voltage of 10 V was applied for 10 seconds, and the bonded body was peeled while the voltage was still applied. The measurement results are shown in Table 2.

[0169] (Adhesive strength reduction rate) The adhesive strength loss rate due to voltage application was calculated using the initial adhesive strength measured by the above method and the adhesive strength during voltage application after storage for 7 days in an environment of 22°C and 15% RH according to the following formula (C). The results are shown in Table 2. Adhesive strength decrease rate (%) = {1-(adhesive strength during voltage application / initial adhesive strength)} x 100 (C)

[0170] [Table 2]

[0171] A pressure-sensitive adhesive layer was formed using the pressure-sensitive adhesive composition, and the pressure-sensitive adhesive layer was rated at A50 in accordance with JIS H4000:2014. After being attached to an aluminum plate made of 52P H32 and left for 7 days in an environment of 22°C and 15% RH, the capacitance per unit area of ​​the interface between the adhesive layer and the aluminum plate was 0.9μF / cm 2 As described above, the pressure-sensitive adhesive compositions of Examples 2-1 to 2-11, in which the pressure-sensitive adhesive layer had an ion conductivity of 10 μS / m or more, all exhibited a large rate of decrease in adhesive strength due to voltage application.

[0172] [Examples 3-1 to 3-5] <Preparation of polymer solution> (Preparation of acrylic polymer 11 solution) As monomer components, 2-methoxyethyl acrylate (MEA): 95 parts by mass and 4-hydroxybutyl acrylate (4HBA): 5 parts by mass were put into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 2,2'-azobisisobutyronitrile (AIBN): 0.2 parts by mass was added as a polymerization initiator, and the temperature was raised to 63°C and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 11 solution with a solid content concentration of 30% by mass.

[0173] <Preparation of Pressure-Sensitive Adhesive Composition> The acrylic polymer solution obtained above, the above-mentioned polymer, crosslinking agent, ionic liquid, additives, or the following additives were added and stirred and mixed to obtain pressure-sensitive adhesive compositions of Examples 3-1 to 3-5. Table 3 shows the amount of each component. (Additives) EMIM-MeSO 3 : Ionic additive, imidazolium salt, manufactured by Tokyo Chemical Industry Co., Ltd. · Epomin 200: Polyethyleneimine, manufactured by Nippon Shokubai.

[0174] <Measurement and evaluation of ionic conductivity and capacitance per unit area of ​​adhesive layer> In the same manner as in Examples 2-1 to 2-11 and Comparative Examples 2-1 to 2-3, the initial adhesive strength, the adhesive strength and adhesive strength loss rate during voltage application after storage for 3 days in an environment of 22°C and 20% RH, and the adhesive strength and adhesive strength loss rate during voltage application after storage for 7 days in an environment of 22°C and 15% RH were measured. In addition, in the same manner as in Examples 2-1 to 2-11 and Comparative Examples 2-1 to 2-3, measurement samples (composite samples) were prepared, and the capacitance of the adhesive interface and the ionic conductivity of the pressure-sensitive adhesive layer were determined. The results are shown in Table 3.

[0175] [Table 3]

[0176] A pressure-sensitive adhesive layer was formed using the pressure-sensitive adhesive composition, and the pressure-sensitive adhesive layer was rated at A50 in accordance with JIS H4000:2014. After being attached to an aluminum plate made of 52P H32 and left for 7 days in an environment of 22°C and 15% RH, the capacitance per unit area of ​​the interface between the adhesive layer and the aluminum plate was 0.9μF / cm 2 As described above, the pressure-sensitive adhesive compositions of Examples 3-1 to 3-5, in which the pressure-sensitive adhesive layer had an ion conductivity of 10 μS / m or more, all exhibited a large rate of decrease in adhesive strength due to voltage application. [Explanation of symbols]

[0177] X1, X2, X3 adhesive sheet 1 Electrically peelable adhesive layer 2 Adhesive layer 3 Base material 4 Conductive layer 5 Base material for current carrying 100 Aluminum-deposited PET film 200 Adhesive layer 300 Aluminum Plate 400 zygote samples

Claims

1. A pressure-sensitive adhesive composition comprising a polymer and an ionic liquid, A pressure-sensitive adhesive composition, in which an adhesive layer is formed from a composition consisting of components other than the ionic liquid among the components contained in the pressure-sensitive adhesive composition, and after the pressure-sensitive adhesive layer is left for 3 days in an environment of 22°C and 20% RH, the pressure-sensitive adhesive layer has a relative dielectric constant of 5 or more at a frequency of 100 Hz.

2. A pressure-sensitive adhesive composition comprising a polymer and an ionic liquid, A pressure-sensitive adhesive layer is formed from the pressure-sensitive adhesive composition, and the pressure-sensitive adhesive layer is subjected to a pressure-sensitive adhesive test according to JIS H4000:2014 A. After being left for 7 days in an environment of 22°C and 15% RH, the capacitance per unit area of ​​the interface between the adhesive layer and the aluminum plate was 0.9 μF / cm 2 The pressure-sensitive adhesive composition as described above, wherein the pressure-sensitive adhesive layer has an ionic conductivity of 10 μS / m or more.

3. A pressure-sensitive adhesive layer is formed from the pressure-sensitive adhesive composition, and the pressure-sensitive adhesive layer is subjected to a pressure-sensitive adhesive test according to JIS H4000:2014 A. After being left for 7 days in an environment of 22°C and 15% RH, the capacitance per unit area of ​​the interface between the adhesive layer and the aluminum plate was 1.2 μF / cm 2 The pressure-sensitive adhesive composition according to claim 2 , wherein the pressure-sensitive adhesive layer has an ionic conductivity of 20 μS / m or more.

4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, further comprising an ionic solid.

5. The pressure-sensitive adhesive composition according to any one of claims 1 to 4, wherein the polymer comprises an ionic polymer.

6. The pressure-sensitive adhesive composition according to any one of claims 1 to 5, wherein the polymer comprises at least one selected from the group consisting of a polyester-based polymer, a urethane-based polymer, and an acrylic polymer having a carboxyl group, an alkoxy group, a hydroxyl group, and / or an amide bond.

7. A polymer and an ionic liquid are included, A pressure-sensitive adhesive composition comprising 0.5 to 30 parts by mass of the ionic liquid and 0.5 to 10 parts by mass of an ionic solid relative to 100 parts by mass of the polymer.

8. A polymer and an ionic liquid are included, The pressure-sensitive adhesive composition comprises 0.5 to 30 parts by mass of the ionic liquid relative to 100 parts by mass of the polymer, and the polymer comprises 0.05 to 2 parts by mass of an ionic polymer.

9. A pressure-sensitive adhesive composition comprising 100 parts by mass of an acrylic polymer and 0.5 to 30 parts by mass of an ionic liquid, wherein a ratio of a polar group-containing monomer to all monomer components constituting the acrylic polymer is 0.1 to 35% by mass.

10. The pressure-sensitive adhesive composition according to any one of claims 1 to 9, which is for electrical peeling.

11. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of claims 1 to 10.

12. A joined body comprising an adherend having a metal adherend surface and the pressure-sensitive adhesive sheet according to claim 11, wherein the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet is joined to the metal adherend surface.

Citation Information

Patent Citations

  • Adhesive composition for polarizing plate and preparation method of the same

    JP2009251281A

  • Electrically peelable adhesive composition, electrically peelable adhesive product and method for peeling the same

    JP2010037355A

  • Adhesive composition, adhesive layer, polarizing film with the adhesive layer, and image-forming device

    JP2013221067A

  • Adhesive composition and surface protective film for optical member

    JP2014148598A

  • Adhesive composition, adhesive tape and laminate

    JP2015129211A

Cited By

  • Non-absorbent cleaning member with transport arm working end coupling element for use in a sample testing system

    US12306091B2